Exploring of the Potential of Parthenium Weed Ash as Substitute for Commercial Alkali for Preparation of Laundry Soap: As a Means to Control Invasion of Parthenium - Adane, Legesse; Gelaye, Tesfaye; Tesfaye, Tegene (Frontiers in Sustainability, 2021)
Alkali solution (of pH 11.9) was prepared from partheniun weed ash. The observed pH value revealed that the prepared lye solution to be potentially suitable for soap making. Similarly, the tests on physicochemical properties of the collected used cooking oil sample were found to be 141.0 ± 0.4-153.8 ± 0.33 mg KOH/g, 11.28 ± 0.5 - 14.1 ± 0.5 mg KOH/g and 0.16 ± 0.2-0.19 ± 0.25 milieq/g for saponification value, acid value and peroxide value, respectively. The data indicated that both the prepared lye solution and the collected used cooking oils to be suitable for soap preparation. Moreover, analyses of the moisture content, total alkali content, total fatty matter, the pH value and chloride content of the prepared soap materials were found to be in the ranges of 10.5 ± 0.01 -13 ± 0.01, 0.39 ± 0.01 - 1.63± 0.05%, 64.5 ± 0.16 -76.4 ± 0.15%, 10.5 ± 0.03 - 10.63 ± 0.04 and 0.39 ± 0.2 - 0.45 ± 0.39%, respectively. The finding of the present study suggested the possibility of controlling parthenium weed invasion by utilizing using it as raw material for soap making. The finding also suggests that preparation of lye solution from parthenium weed ash can be used as an option for controlling pollution of this invasive weed. Moreover, utilization of Parthenium weed ash (or lye solution from this ash) for soap making by treating with used cooking oils not only used to control this invasive weed but also used control environmental pollutions caused by leftovers of used cooking oils.